PERSEPSI GURU DAN SISWA TERHADAP KUALITAS PELAYANAN PERPUSTAKAAN DI SEKOLAH DASAR NEGERI 004 SAMARINDA ULU - Gustiawan, Fathan; Eka Wardhana, Kautsar (Journal of Sustainable Transformation, 2024)
This study aims to explore the perceptions of teachers and students towards library services at school. The method was descriptive qualitative, with data collection through in-depth interviews and observation. The research subjects comprised 3 teachers and 2 students at 004 Elementary School of  Samarinda Ulu. This study used triangulation to analyze the data studied. The results showed that teachers view library services as an important resource for learning. They appreciate the availability of books and adequate facilities. Still, they would like improvements in the availability of the latest book services and the internet network, thus the students could get information easily in learning. On the other hand, students show enthusiasm for the library but complain about the lack of variety of reading topics and room for reading. Based on this information, the recommendation for library services is to improve library management to support the learning process and literacy and develop programs for improving student attractiveness. Thus, library services can be optimized.